2001
DOI: 10.1002/mrc.852
|View full text |Cite
|
Sign up to set email alerts
|

Oxazine‐ and oxazole‐fused derivatives of the alkaloid boldine and their complete structural and spectral assignments by HMQC and HMBC experiments

Abstract: The novel heterocycles 1,11-dimethoxy-2-hydroxy-6-methyloxazolo[4,5-k]-5,6,6a,7-tetrahydro-4H-dibenzo [de,g]quinoline, 1,12-dimethoxy-2-hydroxy-6-methyl-9-phenyl-10H-oxazin[5,6-k]-5,6,6a,7-tetrahydro-4H-dibenzo[de,g]quinolin-10-one and 1,11-dimethoxy-2-hydroxy-6-methyl-9-phenyloxazolo[4,5-k]-5,6,6a,7-tetrahydro-4H-dibenzo[de,g]quinoline were prepared starting from the alkaloid boldine. The structures were confirmed and the 1 H and 13 C NMR spectra were completely assigned using a combination of one-and two-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…(S)-Glau-cine was treated similarly to obtain compounds 12 and 13. (S)-8-NO-Boldine was obtained by nitrosation of (S)-boldine with NaNO 2 in AcOH, and (S)-8-NH 2 -boldine was prepared by catalytic hydrogenation of (S)-8-NO-boldine [18]. Alkaloid solutions were prepared daily in deionised water with 0.1 % (w/v) ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…(S)-Glau-cine was treated similarly to obtain compounds 12 and 13. (S)-8-NO-Boldine was obtained by nitrosation of (S)-boldine with NaNO 2 in AcOH, and (S)-8-NH 2 -boldine was prepared by catalytic hydrogenation of (S)-8-NO-boldine [18]. Alkaloid solutions were prepared daily in deionised water with 0.1 % (w/v) ascorbic acid.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Hydrochloride salts were prepared by dissolving the compounds in isopropanol and subsequently adding HCl to precipitate the hydrochloride with ethyl ether.…”
Section: Methodsmentioning
confidence: 99%
“…One way of achieving this would be to replace the aromatic ring hydrogens with not very bulky substituents that would be expected to make a positive contribution to the overall lipophilicity. 17 An important part of the deleterious effects of exposing skin to solar UV radiation is attributed to the generation of reactive oxygen species (i.e. singlet oxygen, superoxide and hydroxyl radicals).…”
Section: Introductionmentioning
confidence: 99%
“…The O-methylation of boldine with diazomethane allows the 9-O-methyl derivative predicentrine to be isolated in addition to the di-O-methylated glaucine, apparently due to the more rapid reaction of the C-9 hydroxyl group because of its greater acidity and/or its greater exposure due to the preferred coplanarity of the C-10 methoxyl group with aromatic ring D, in contrast to the necessarily perpendicular arrangement of the C-1 methoxyl group as a consequence of its compression between the C-2 hydroxyl and the C-11 hydrogen [27,28]. The same protocols used before for boldine, glaucine and the haloboldines showed that predicentrine has marginal D1-like dopamine receptor selectivity, but its 3-bromo-and iodo derivatives, though somewhat less potent than 3-iodoboldine, exhibit about 41-fold and 139-fold preferences for the D1-like receptor [17] ( Boldine undergoes facile nitrosation with sodium nitrite in acetic acid to afford 8-nitrosoboldine and, after catalytic hydrogenation, 8-aminoboldine [29]. Radioligand displacement by these two derivatives showed that the 8-amino compound binds with negligible selectivity to both major dopamine receptor families and with slightly lower affinities than boldine, while 8-nitrosoboldine binds rather strongly to D1-like receptors (IC 50 = 34 nM) with more than 200-fold selectivity over D2-like receptors [16] (Table 1).…”
Section: Dopaminergic Activitymentioning
confidence: 99%